Lobbying: Buying and utilizing access - Wolfgang Mayer; Sudesh Mujumdar (Kiel Institute for the World Economy (IfW), 2012)
This paper introduces an alternative to the lobbying literature's standard assumption that money buys policies. Our model - in which influence-seeking requires both money to buy access and managerial time to utilize access - offers three significant benefits. First, it counters criticism that the money-buys-policies assumption is at odds with reality. Second, its much stronger lobbying incentives weaken the free-rider problem and raise incentives for lobby formation. Third, the model yields testable hypotheses on: the determinants of lobbying incentives; the number of lobbying firms in an industry; and the impact on industry lobbying by the size distribution of firms, contribution limits on firms, world price changes, and the ability to adjust labor employment.
Keywords: F16; H0; L1; 330; lobbying; free-rider problem; size-distribution-of-firms; world-price; labor-market-flexibility; Interessenpolitik; Ökonomischer Anreiz; Interessenvertretung; Trittbrettfahrerverhalten; Betriebsgrößenstruktur; Außenhandelspreis; Arbeitsmarktflexibilität; Theorie